Perfect Absorption for Modulus-Near-Zero Acoustic Metamaterial in Air or Underwater at Low-Frequency - Fatma Nafaa Gaafer (Archives of Acoustics, 2022)
We theoretically propose a method to achieve an optimum absorbing material through a modulus-near-zero (MNZ) metamaterial immersed in air or water with a change in slit width part. The destructive interference has paved the way to achieve perfect absorption (PA). Depending upon theoretical analysis, an acoustic metamaterial (AMMs) that supports resonance with a monopole (140 Hz) is developed to construct a low-frequency sound-absorbing technology. The dissipative loss effect can be by attentively controlling onto slit width to achieve perfect absorption. When there are thin slit width and visco-thermal losses in the structure, it is observed that they lead to high absorption. We use finite element simulations via COMSOL Multiphysics software to theoretical measurement in impedance tube and show the influence of structural parameters in both mediums. The results are of extraordinary correspondence at low frequency to achieve optimum perfect absorption (99%). That might support AMMs to actual engineering-related applications in the process of mitigating noise, slow sound trapping, notch filtering, energy conversion, and time reversal technology.